2020
DOI: 10.1038/s12276-020-0429-6
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic diversity of RNA variants and RNA variation-associated factors in cancer development

Abstract: Recently, with the development of RNA sequencing technologies such as next-generation sequencing (NGS) for RNA, numerous variations of alternatively processed RNAs made by alternative splicing, RNA editing, alternative maturation of microRNA (miRNA), RNA methylation, and alternative polyadenylation have been uncovered. Furthermore, abnormally processed RNAs can cause a variety of diseases, including obesity, diabetes, Alzheimer's disease, and cancer. Especially in cancer development, aberrant RNAs caused by de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 106 publications
(106 reference statements)
0
15
0
Order By: Relevance
“…Also, the RNA Binding Proteins (RBPs), which plays a major role in temporal and spatial organization of RNA in the cell, mutated RBPs are significantly influencing the final RNAs expression. Moreover, the small size of the cytoplasm, and organelles, the aberrant splicing, loss of polarity of cytoskeleton, adhesion molecules (stickiness), with poorly defined tumor boundaries, and overall loss of normal cell specialized cell features, with immature differentiation of cancer cell, high rate of cell division, results in the presence of RNAs (coding and non-coding), with many mutations and inappropriate spatial organization, and affecting RNA stability thus, affecting the final RNA folding(tertiary structure) [ 19 , 77 , 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the RNA Binding Proteins (RBPs), which plays a major role in temporal and spatial organization of RNA in the cell, mutated RBPs are significantly influencing the final RNAs expression. Moreover, the small size of the cytoplasm, and organelles, the aberrant splicing, loss of polarity of cytoskeleton, adhesion molecules (stickiness), with poorly defined tumor boundaries, and overall loss of normal cell specialized cell features, with immature differentiation of cancer cell, high rate of cell division, results in the presence of RNAs (coding and non-coding), with many mutations and inappropriate spatial organization, and affecting RNA stability thus, affecting the final RNA folding(tertiary structure) [ 19 , 77 , 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, yang et al, have shown that cancer progression is governed by the presence of numerous altered RNA molecules of different types (coding and non coding) such as up-normal splicing, methylation, alteration in the 3′UTR of mRNAs (variants/alternative polyadenylations), in addition to, numerous heterogeneity in miRNAs and LncRNAs sequences, expression and modifications, which affects significantly the cell dogma RNAs structure, maturation, stability, decay and translation [ 18 ]. Moreover, these mutations, differential expression and the interactions with miRNAs, LncRNAs and mRNA are affecting significantly the initiation, and progression of HCC to metastasis [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plec was also reported as essential to the integrity of muscle cells in epithelial cells [ 19 ], and vital to the crosslinking of actin filaments and microtubules in the nervous system [ 20 ]. The protein serine and arginine-rich splicing factor 1 (Srsf1) is a proto-oncogene [ 21 ] that can act as an oncoprotein, and is an important target for cancer therapy, as it is overexpressed in many tumors [ 22 ]. Extracellular matrix molecules, including fibronectin, have been identified as activators of the toll-like receptors that function as regulators of the innate immune system in response to pathogens and damaged tissue [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, there are multiple mechanisms that oncoviruses employ to overhaul the splicing and epigenetic machinery to induce carcinogenic effects. Oncoviruses can influence splicing and epigenetics through indirect mechanisms such as introducing mutations in and modulating the expression of splicing factors, post-transcriptional modifications, including phosphorylation and polyadenylation, and modulating the localisation of splicing factors [ 20 , 108 ]. In addition, oncoviruses can regulate epigenetic alternations by inducing histone modification.…”
Section: Viral Infection Epigenetics and Aberrant Splicingmentioning
confidence: 99%
“…In addition, oncoviruses can regulate epigenetic alternations by inducing histone modification. Alternative splicing of RNA can be affected by histone modification that occurs in close proximity to splice site regions [ 108 ]. Consequently, the loss of stringent regulation in RNA splicing and epigenetic mechanisms resulting in carcinogenesis which is attributed to aberrant RNA transcripts that are translated to viral and cellular oncoproteins.…”
Section: Viral Infection Epigenetics and Aberrant Splicingmentioning
confidence: 99%